Characteristics of lactic acid bacteria isolated from different sources and their effects on the silage quality of oat (Avena sativa L.) straw on the Tibetan Plateau. (20th November 2017) - Wang, Siran; Yuan, Xianjun; Dong, Zhihao; Li, Junfeng; Shao, Tao
Abstract: Eight lactic acid bacteria (LAB) strains isolated from five naturally‐fermented silages of different ensilage materials on the Tibetan Plateau were characterized and their effects on the silage quality of oat ( Avena sativa L.) straw were studied. These LAB isolates were evaluated using morphological, physiological and biochemical tests. All eight strains (M1, LM8, LO7, LOG9, LCG3, LTG7, I5 and LI3) could grow at 5–20°C, pH 3.5–7.0 and NaCl (3.0, 6.5%) and they were identified as Lactobacillus plantarum, L. coryniformis, Pediococcus pentosaceus, P. acidilactici, L. plantarum, P. acidilactici, L. paraplantarum and L. casei by sequencing 16S rDNA, respectively. The eight isolated strains and one commercial inoculant ( L. plantarum MTD‐1) were subsequently added to oat straw for ensiling 35 days. All the LAB strains improved the silage quality of oat straw, evidenced by significantly ( P < 0.05) higher lactic acid (LA) and residual water soluble carbohydrate (WSC) contents and ratios of LA to acetic acid (LA/AA), and significantly ( P < 0.05) lower pH and ammonia nitrogen contents. 'LOG9' performed best among all LAB strains, evidenced by the highest ( P < 0.05) LA (94.19 g kg −1 dry matter [DM]) and residual WSC contents (44.53 g kg −1 DM) and ratio of LA/AA (18.18) and LAB count (8.86 lg cfu g −1 fresh weight), and the lowest ( P < 0.05) pH (3.87), this might be related to its host specificity. Strain LOG9 is recommended as starter culture for oat straw silage.